Legal Certainty and Protection for Online Motorcycle Taxi Drivers in Indonesia: A Normative Analysis of Unilateral Termination under Regulation No. 12/2019 - Pinta Cahya Thamrin; Astrid Amidiaputri Hasyyati (Greenation International Journal of Law and Social Sciences, 2026)
The phenomenon of unilateral termination of online motorcycle taxi drivers has increasingly occurred. This situation indicates that the position of online motorcycle taxi drivers as partners is very weak, as such clauses are contained in partnership agreements. This study discusses the legal regulation of online motorcycle taxi drivers viewed from partnership-based agreements and the unilateral termination of Gojek drivers reviewed from Minister of Transportation Regulation Number 12 of 2019. The research method employed is normative juridical research. Data were collected through library research. The collected data were then analyzed qualitatively to obtain descriptive research results. The findings show that the regulations governing partnership agreements between online motorcycle taxi drivers and providers have not yet specifically regulated the provisions of such cooperation agreements. Currently, the legal basis governing partnership agreements refers only to the provisions of the Civil Code, the Law on Micro, Small, and Medium Enterprises, and Minister of Transportation Regulation Number 12 of 2019. However, there is no specific regulation governing the partnership relationship between drivers and online motorcycle taxi service providers. The scientific contribution of this research lies in its conceptualization of platform-based partnerships as a distinct legal regime requiring sui generis regulation. It advances the argument that the current classification of drivers as “partners” constitutes a legal fiction that obscures asymmetrical power relations. Accordingly, this study proposes the necessity of a dedicated regulatory framework that integrates principles of contractual fairness, procedural due process, and digital labor protection to ensure a more balanced and equitable legal relationship between platform providers and drivers.